1997
DOI: 10.1046/j.1365-2648.1997.1997025942.x
|View full text |Cite
|
Sign up to set email alerts
|

A small exploratory study of the reaction of older people to an episode of delirium

Abstract: Delirium or an acute confusional state, occurs as a result of disease or physiological imbalance secondary to impaired brain function. One of its main clinical features is widespread cognitive impairment, which causes patients to become disconnected from their immediate surroundings and misinterpret reality. It has a sudden onset and its duration is relatively brief. Some authors take the view that delirium might be interpreted as a precursor to dementia. The aim of the study was to retrospectively explore old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(73 citation statements)
references
References 14 publications
3
68
2
Order By: Relevance
“…This may well have influenced what the patients revealed during the interviews and their capacity to retell and remember. Earlier studies (Laitinen, 1996;Schofield, 1997) have shown that the patients did not remember particularly well. In these studies, however, the patient and the interviewer met only after the patient was lucid again.…”
Section: Methodological Considerationsmentioning
confidence: 82%
“…This may well have influenced what the patients revealed during the interviews and their capacity to retell and remember. Earlier studies (Laitinen, 1996;Schofield, 1997) have shown that the patients did not remember particularly well. In these studies, however, the patient and the interviewer met only after the patient was lucid again.…”
Section: Methodological Considerationsmentioning
confidence: 82%
“…Family involvement is especially important because older patients and their families often have unarticulated fears that an episode of delirium is an indication of impending or developing dementia. 68 This problem is compounded if patients remember their delirium experience; they require further reassurance that the delirium is a transient cognitive impairment related to their physical illness.…”
Section: No (%)mentioning
confidence: 99%
“…Recovered patients are often uncomfortable discussing the experience, but most do recognise its transient nature (Schofield, 1997). Simple clarification can reduce the likelihood of patients or their relatives misinterpreting an episode of delirium as evidence of brain damage or as the first step towards senility or madness.…”
Section: Psychiatrists' Expertise In Delirium Managementmentioning
confidence: 99%